Effects of bone marrow mesenchymal stem cells on repair and receptivity of damaged endometrium in rats. Issue 9 (28th June 2021) - Wang, Guiling; Ren, Chun'e; Jiang, Junyi
Abstract: Aim: This study was to investigate whether bone marrow mesenchymal stem cells (BMSCs) can repair damaged endometrium in rats and its effect on endometrial receptivity. Methods: A rat model of endometrial damage was established by heat injury. BMSCs were labeled with PKH26 and were transplanted into the right uterine cavity. The endometrial thickness and fertility testing were examined to assess the repair of damaged endometrium. The mass on trichrome staining was used to assess the endometrium fibrosis. The expression of integrin avβ3 and leukemia inhibitory factor (LIF) in rat endometrium was used to evaluate the endometrial receptivity. Results: After transplantation of BMSCs, the distribution of PKH26 positive cells was mainly on the damaged side in the endometrial tissues. Compared to control group, the endometrial tissue structure recovered after treatment with BMSCs. BMSCs transplantation improved the fertility of endometrial injury model rats. BMSCs decreased the area of endometrial fibrosis. The expression of integrin avβ3 and LIF in endometrium was the stronger in BMSCs treatment group than control group. Conclusion: BMSCs can migrate to the endometrium and repair damaged endometrium and improve endometrium receptivity.